Incorporating macadamia oil and butter to reduce dietary omega‐6 polyunsaturated fatty acid intake. Issue 2 (4th June 2013) - Wood, Katie E.; Mantzioris, Evangeline; Gibson, Robert A.; Muhlhausler, Beverly S.
Abstract: Aim: Claims have been made that the level of omega‐6 fats in the diet is too high and that this cannot be reduced without increasing the saturated fat intake. The aim of this study was to design a diet within the framework of the Australian Guide to Healthy Eating (AGHE) which would supply <2% energy (% E) from the omega‐6 polyunsaturated fatty acid (PUFA), linoleic acid, compared with the 4–5% E in the current Australian diet. Methods: Separate seven‐day diet plans were designed using FoodWorks (version 2009) for males (10 000 kJ)/day) and females (8000 kJ/day). The reduction in dietary omega‐6 PUFA content was achieved by replacing standard plant‐based oils and spreads used in cooking and baking (canola and sunflower oils) with macadamia oil and butter, and restricting the intake of some processed foods. All diets complied with the AGHE. Results: We successfully designed diets which complied with the AGHE and which had a linoleic acid (LA) content of 1.80% E and 1.75% E in females and males, respectively. In both cases, the omega‐6 : omega‐3 ratio was reduced to 5.1:1, compared with ∼12:1 in the typical Australian diet, and the saturated fat content was <10% E. Conclusion: These results suggest that reducing the LA content of the diet can be readily achieved within the boundaries set by the AGHE, without an increase in saturated fat intake.